Noncoding RNAs in vascular smooth muscle cell function and neointimal hyperplasia - Maguire, Eithne Margaret; Xiao, Qingzhong (The FEBS journal, 2020)
Neointimal hyperplasia (NIH) is a pathological process occurring in the blood vessel wall during atherosclerosis and in‐stent restenosis (ISR). Due to the abundance of vascular smooth muscle cells (VSMCs) within neointimal lesions, VSMCs have long been considered as a key cellular target in preventing NIH. Noncoding RNA molecules such as microRNA (miRNAs), long noncoding RNA (lncRNAs) and circular RNAs (circRNAs) expressed in VSMCs offer unique therapeutic targets for tackling VSMC phenotype switching, proliferation, migration and apoptosis processes responsible for promoting NIH. In this review, we provide an extensive overview of VSMC RNA biology, highlighting the most recent discoveries in the field of lncRNAs and circRNAs, with the aim of identifying key molecular players that could be harnessed for future therapeutic interventions, in our quest to halt NIH in vascular disease. Previously considered as ‘junk RNAs’, emerging evidence has established numerous noncoding RNAs (ncRNAs) as masters controlling smooth muscle cell (SMC) phenotypes and functions (phenotype switching, apoptosis, proliferation and migration, inflammatory response). This Review provides an extensive overview of SMC ncRNA biology, highlighting the most recent discoveries in the field of ncRNAs, with the aim of identifying key ncRNAs that could be harnessed for future therapeutic interventions in vascular disease.